A summative content analysis of how programmes to improve the right to sexual and reproductive health address power - Marta Schaaf; Victoria Boydell; Stephanie M. Topp; Aditi Iyer; Gita Sen; Ian Askew (BMJ Glob. Health, 2022)
Introduction Power shapes all aspects of global health. The concept of power is not only useful in understanding the current situation, but it is also regularly mobilised in programmatic efforts that seek to change power relations. This paper uses summative content analysis to describe how sexual and reproductive health (SRH) programmes in low-income and middle-income countries explicitly and implicitly aim to alter relations of power. Methods Content analysis is a qualitative approach to analysing textual data; in our analysis, peer-reviewed articles that describe programmes aiming to alter power relations to improve SRH constituted the data. We searched three databases, ultimately including 108 articles. We extracted the articles into a spreadsheet that included basic details about the paper and the programme, including what level of the social ecological model programme activities addressed. Results The programmes reviewed reflect a diversity of priorities and approaches to addressing power, though most papers were largely based in a biomedical framework. Most programmes intervened at multiple levels simultaneously; some of these were 'structural' programmes that explicitly aimed to shift power relations, others addressed multiple levels using a more typical programme theory that sought to change individual behaviours and proximate drivers. This prevailing focus on proximate behaviours is somewhat mismatched with the broader literature on the power-related drivers of SRH health inequities, which explores the role of embedded norms and structures. Conclusion This paper adds value by summarising what the academic public health community has chosen to test and research in terms of power relations and SRH, and by raising questions about how this corresponds to the significant task of effecting change in power relations to improve the right to SRH.
Keywords: Abortion; Reproductive health; Young women